Causality between ischemic stroke and epilepsy based on Mendelian randomization - SHU Yun; SHU Yun; YUAN Qing; WU Zhifeng (陆军军医大学学报)
Objective To explore the causal relationship between ischemic stroke and different types of epilepsy so as to provide genetic evidence for the risk of epilepsy after ischemic stroke. Methods Based on the summary data of genome-wide association study, Mendelian randomization (MR) analysis was performed with MR-Egger regression, weighted median and inverse-variance weighting. Sensitivity analysis was conducted by using MR-Egger regression test, MR-PRESSO test and leave-one-out method. Results Two-sample MR analysis showed that there was a causal relationship between ischemic stroke and the risk of epilepsy (OR=1.10, P=0.036) and generalized epilepsy (OR=1.25, P=0.001), but no such relationship was observed with the risk of focal epilepsy (OR=1.06, P=0.360). In addition, diastolic blood pressure (OR=1.12, P=0.002) and BMI (OR=1.08, P=0.015) also had a causal relationship with the risk of epilepsy. After adjusting confounding factors, multivariate MR analysis revealed that only ischemic stroke (OR=1.18, P=3.770×10-6) and epilepsy risk had a causal relationship. Conclusion There is a causal relationship between ischemic stroke and the risk of generalized epilepsy, which can be used to stratify the risk of post-stroke epilepsy.